Measurement of fiducial and differential W+W- production cross-sections at √s=13 TeV with the ATLAS detector - Aaboud, Morad; Andrei, George Victor; Bolz, Arthur; Dunford, Monica; Ferreira de Lima, Danilo Enoque; Franchino, Silvia; Helary, Louis; Krishnan, Anjali; Kugel, Andreas; Napolitano, Fabrizio; Schöning, André; Schultz-Coulon, Hans-Christian; et al. (The European physical journal. C, Particles and fields, 2019)
A measurement of fiducial and differential cross-sections for W+W−W+W−W^+W^- production in proton-proton collisions at s√=13s=13\sqrt{s}=13 TeV with the ATLAS experiment at the Large Hadron Collider using data corresponding to an integrated luminosity of 36.1 fb−1fb−1\hbox {fb}^{-1} is presented. Events with one electron and one muon are selected, corresponding to the decay of the diboson system as WW→e±νμ∓νWW→e±νμ∓νWW→ e^{± }ν μ ^{\mp }ν . To suppress top-quark background, events containing jets with a transverse momentum exceeding 35 GeV are not included in the measurement phase space. The fiducial cross-section, six differential distributions and the cross-section as a function of the jet-veto transverse momentum threshold are measured and compared with several theoretical predictions. Constraints on anomalous electroweak gauge boson self-interactions are also presented in the framework of a dimension-six effective field theory.